(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present research aims to identify The Effectiveness of Using The Design Thinking Model in Mathematics Achievement and Productive Thinking Skills Among First Intermediate Class Females Students. The sample of the research was intentionally chosen and it was represented by females students of the first intermediate grade in (Elaaf Secondary Girls School) followed to the General Directorate of Education in Baghdad / Rusafa 2nd, and the sample consisted of (50) students (after excluding repeated). (24) female students who were studied according to the design thinking model, and Division (C) to represent the control group with (26) students who were studied according to the usual method. previous achievement in mathematics, previous information in mathematics, and productive thinking). The experiment was conducted in the first semester (first course) of the academic year (2020-2021) and on the semesters (Semester Two: Rational Numbers, Chapter Three: Polynomials, and Chapter Four: Open Sentences), from the mathematics book for the first intermediate grade, Part 1. Edition 4, year (2019), and the researcher adopted the experimental method, and the two research tools were prepared: the achievement test according to Bloom levels (remember, comprehension, application, analysis, synthesis, and evaluation) consisting of (30) paragraphs of the type of multiple choice with four alternatives And using the Keoder Richardson equation (KR-20), the value of the reliability coefficient was (0.84), and the productive thinking test consisted of (30) items (15) items of the multiple-choice type, and (15) essay items, and using the equation (Alpha - Cronbach) The value of the reliability coefficient was (0.88), and after applying the test and processing the data statistically using the t-test for two independent samples and the Levens’ test, the results resulted in the following: There is a statistically significant difference between the experimental and control groups in the achievement tests and productive thinking skills in favor of the experimental group. In light of the results of the research, the researcher recommended teaching mathematics at different academic levels according to the design thinking model and conducting training courses for mathematics teachers on the use of various models in teaching, including the design thinking model, and suggests conducting a study similar to the current study on other variables such as complex thinking skills and skills. Mathematical communication or behavioral variables such as tendencies or attitudes towards mathematics.